A comparison of different heart rate deflection methods to predict the anaerobic threshold - Carey, D. G.; Pliego, G. J.; Raymond, R. L. (European Journal of Sport Science, 2008)
There is perhaps no greater controversy in exercise physiology than the validity, or lack thereof, of the heart rate breakpoint theory in general, and the Conconi test in particular, in assessing the anaerobic threshold. Three heart rate breakpoint methods have been proposed as methods of detecting the anaerobic threshold have appeared in the literature: (1) a breakpoint in linearity of the heart rate-work rate relationship (heart rate breakpoint); (2) a log function curve of the heart rate-work rate relationship (log function); and (3) a combination of linear regression and logarithmic function of the heart rate-work rate relationship (log-linear). The main aim of this study was to assess the validity of these methods compared with that of gas analysis assessment of the anaerobic threshold. This was a descriptive study of 115 endurance athletes undergoing simultaneous gas analysis and heart rate determination during incremental exercise to exhaustion. The participants were 115 competitive cyclists and/or triathletes (71 males: mean age 38.5 years, s=6.2; 44 females: mean age 37.8 years, s=5.1). Incremental exercise testing to exhaustion was performed on an electrically braked cycle ergometer, commencing at 25 W and increasing by 25 W · min-1 to volitional fatigue. Heart rate was recorded each minute and at exhaustion. Gas analysis was performed using breath-by-breath analysis with 10-s averaging. The anaerobic threshold based on ventilatory parameters was used as the criterion test. Compared with the criterion threshold, no significant differences were observed for the heart rate breakpoint (t=1.12, P=0.268) or log function (t=0.0, P=0.998) methods. However, the log-linear method (t=2.25, P=0.026) significantly overestimated the anaerobic threshold. Although two of the three heart rate methods were validated in this study, the relatively large total errors for these methods (13.7 beats · min-1 for heart rate breakpoint, 12.5 beats · min-1 for log function, and 14.3 beats · min-1 for log-linear) indicate that they would have little practical value.